ANALISIS KETEPATAN SASARAN PENYALURAN BANTUAN PROGRAM KELUARGA HARAPAN DI DINAS SOSIAL KOTA GUNUNGSITOLI - Ernila Mei Salirani Telaumbanua; Eliagus Telaumbanua; Serniati Zebua; Meiman Hidayat Waruwu (Jurnal Publikasi Manajemen Informatika, 2026)
The Family Hope Program (PKH) is an initiative of the Indonesian government aimed at reducing poverty through conditional cash transfers. The program is designed to improve poor families’ access to health, education, and social welfare services. However, despite its implementation, there are still indications of targeting inaccuracies in the distribution of assistance, such as benefits received by households that do not meet the criteria, while eligible families remain unregistered. This study employs a qualitative method with a case study approach to gain an in-depth understanding of the targeting accuracy of PKH assistance distribution in Gunungsitoli City. The case study method was chosen as it allows the researcher to comprehensively explore how PKH assistance is distributed, how beneficiary criteria are applied, and what factors influence the program’s effectiveness in achieving its intended goals. The findings reveal that the targeting accuracy of PKH assistance distribution in Gunungsitoli City is relatively good, although several challenges remain. The study identifies key factors that potentially reduce targeting accuracy, including delays in data updating, limited inter-agency coordination, low beneficiary awareness in reporting changes, and the shortage of facilitators. To improve targeting accuracy, the Social Service Office of Gunungsitoli has undertaken efforts such as periodic data verification and validation, strengthening coordination among stakeholders, and encouraging greater community participation.